As contribuições da educação continuada em disfagia para a assistência de enfermagem pediátrica em um hospital de ensino - Leonor, Verena dias (2014)
INTRODUCTION: the diagnosis and nursing care for patients with dysphagia are important for the treatment and rehabilitation contribution of these. Continuing education has a paramount roleto base the actuation of these professionals in a multidisciplinary staff, amending at reducing morbidity and mortality caused bydysphagia, with the management of disorders, with the management of swallowing disorders under the responsibility of the speech-language. OBJECTIVE: propose educational activity for dysphagia in pediatric nursing staff in a teaching hospital.METHODOLOGY: study of cross delineation quantitative approach. The study was performed in a tertiary reference hospital, entailed to the Unified Health System (SUS). The sample consisted of 62 professionals including nurses, technicians and nursing assistants who work in the care of pediatric patients. We applied a questionnaire for verification ofknowledge about dysphagia later an educational activity and its immediate evaluation was performed. RESULTS: knowledge of nursing dysphagia was evidenced as positive, especially regarding the concept with 96.77% of hits, symptoms with 83.87% of hits, causes with 74.19% of hits, consequences with 70.97% of hits, identification of a qualified professional for rehabilitation with 85.48% accuracy and importance of rehabilitation with 87.10% of hits. Research participants were receptive to educational action taken individually through folder and then posters. In the immediate evaluation after they reported that the intervention had expanded the knowledge about dysphagia, recognized the importance of these and would like to receive more information about this andother pathologies. CONCLUSION: the study demonstrated the fragmented nursing knowledge about dysphagia, but with interest and disposition to learn if content available through continuing education.